Improving Work-Life Balance via Tactical Approaches: Insights from the Automotive Industry - Serpian Serpian; Dian Gita Utami; Syamsuddin Syamsuddin (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Work-life balance (WLB) is increasingly recognized as a critical factor in employee well-being and organizational performance, particularly in high-demand industries such as the automotive sector, where operational pressures often conflict with employees’ personal needs. Objective: This study aims to evaluate how employees in the automotive industry perceive work-life balance (WLB) and to determine the critical aspects requiring improvement to ensure that organizational policies more effectively meet workforce needs. Methods: This study used a quantitative survey of 128 employees in the automotive sector to assess the perceived importance and actual performance of various WLB factors. The data were analyzed using Importance–Performance Analysis (IPA) to identify priority areas and correlations among WLB components. Results: The findings revealed that organizational performance (M = 3.74) exceeded the importance attributed to WLBdimensions (M = 3.63), indicating that overall organizational delivery met employee expectations. IPA revealed two critical gaps in Quadrant I (high importance/low performance) requiring immediate intervention, while six attributes in Quadrant II represented key organizational strengths. Correlation analysis identified eleven statistically significant tactical strategies linking organizational strengths to priority improvement areas. Conclusion: This study offers a novel integration of IPA and correlational analysis to generate eleven evidence-based tactical decisions for WLB enhancement in the automotive sector, thereby advancing both theoretical understanding and practical human resource management.